Impact of digital health on Type 2 diabetes management: a randomised controlled trial of the ‘TreC Diabete’ platform (TELEMECHRON Study) - Alexia Giovanazzi; Lorenzo Gios; Maria Adalgisa Gentilini; Marina Mastellaro; Patrizia Bartolotta; Lucrezia Nicolussi Giacomaz; Claudio Eccher; Sandro Inchiostro (Frontiers in Clinical Diabetes and Healthcare)
BackgroundThe use of technologies in the health field has progressively increased. Within the context of a broader project funded by the Italian Ministry of Health (TELEMECHRON study), a randomised controlled trial (RCT) has been conducted in the Autonomous Province of Trento on type 2 diabetes individuals with an untargeted glycated haemoglobin (HbA1c) level.MethodsThe overall aim was to evaluate the impact of the “TreC Diabete” digital platform, including a smartphone application (app) and a dashboard. This open-label, parallel-group, 1:1 allocation ratio RCT in which the intervention group used the app for data entry, symptoms questionnaire, communication with healthcare staff and medication recording, while the control group received standard care. The primary endpoint was change in HbA1c levels at 12 months between groups.ResultsBetween December 2022 and August 2023, 103 participants were enrolled (51 intervention; 52 control), with a median age of 67 years old, time from diabetes diagnosis to enrolment 13 years, and 72% male. At 12 months, the median change in HbA1c levels did not differ significantly between groups. Regarding app usage, data entries decreased significantly from the first quarter to the second quarter but subsequently stabilised (p = 0.001). System usability (from 42 responders in the intervention group) had a median score of 95 (range: 0–100), indicating a high level of satisfaction with the platform.DiscussionThe study faced several challenges, including platform technical issues, service interruption, data entry anomalies and difficulties in participant recruitment. Study generalisability may be limited by the sample’s demographics, as the trial predominantly included younger male individuals with a specific HbA1c level.ConclusionThe study highlighted key factors for future implementations, including understanding technology benefits, addressing adoption barriers, and providing education and support to both patients and healthcare providers.